Pengaruh Dana Pensiun terhadap Keberlanjutan Fiskal - Alinda Maharani (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2025)
This study investigates the impact of pension fund schemes on fiscal sustainability. The data used is time data for the period 2006 - 2022 using ECM analysis technique. The research found that pension scheme affects fiscal sustainability.